Antistatic resin composition and molded body thereof

The antistatic resin composition, comprising wood flour, a specific polymer compound, and an alkali metal salt or ionic liquid, addresses the shortcomings of conventional antistatic resin compositions by enhancing antistatic performance, durability, and maintaining the wood texture of molded bodies.

JP2025042670APending Publication Date: 2025-03-28ADEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023149728
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Conventional resin molded bodies with antistatic agents lack sufficient antistatic performance and durability, and may damage the wood texture, even when a large amount of antistatic agent is used.

Method used

An antistatic resin composition comprising 1 to 200 parts by mass of wood flour, 1 to 60 parts by mass of a polymer compound obtained by reacting a diol, a dicarboxylic acid, a polyether with hydroxyl groups, and an epoxy compound, and 0.01 to 15.0 parts by mass of an alkali metal salt or ionic liquid based on 100 parts by mass of polyolefin resin.

Benefits of technology

The composition provides a molded body with excellent antistatic properties, durability, and an intact wood texture, effectively addressing the limitations of conventional antistatic resin compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042670000001
    Figure 2025042670000001
  • Figure 2025042670000002
    Figure 2025042670000002
  • Figure 2025042670000003
    Figure 2025042670000003
Patent Text Reader

Abstract

To provide an antistatic resin composition capable of providing a molded body having an excellent woody feeling and excellent antistatic properties and persistence thereof and to provide a molded body having an excellent woody feeling and excellent antistatic properties and persistence thereof.SOLUTION: There is provided an antistatic resin composition which comprises 1 to 200 pts.mass of the following component (X), 1 to 60 pts.mass of the following component (Y) and 0.01 to 15.0 pts.mass of the following component (Z) based on 100 pts.mass of a polyolefin-based resin. Component (X): a wood flour. Component (Y): an antistatic agent containing one or more polymer compounds (E) obtained by the reaction of a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends and an epoxy compound (D) having two or more epoxy groups, in which a polyether (b) having hydroxyl groups at both ends is a polyethylene glycol (b1) and a polytetramethylene glycol (b2) and the ratio of the polytetramethylene glycol (b2) is 10 to 80 mol% based on the total mole number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Z): one or more selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antistatic resin composition (hereinafter also simply referred to as a "resin composition"). More specifically, the present invention relates to an antistatic resin composition capable of providing a molded article having a wood-like texture and excellent antistatic properties, and a molded article having a wood-like texture and excellent antistatic properties. [Background technology]

[0002] In recent years, polyolefin resin molded articles that have a wood-like texture and a color tone and texture similar to natural wood by adding wood powder to polyolefin resins such as polyethylene resins have been widely used. These resin molded articles with a wood-like texture are used, for example, for interior materials for vehicles, side moldings, interior materials for houses, louvers, building materials such as exterior building materials, floor materials such as verandas, terraces, balconies, and deck materials, fence materials, handrail materials, bridges, civil engineering materials, boardwalks across wetlands in natural parks, table frames, gaskets, etc. These resin molded products are easily charged with electricity due to friction, etc., because the polyolefin resin itself has high electrical insulation properties. Once charged with static electricity, the product will discharge when dust adheres to it or the human body comes into contact with it, causing discomfort to people.

[0003] To solve the above problems, antistatic agents made of surfactants have been conventionally blended into resins (Patent Document 1). When blended by kneading, antistatic agents made of surfactants bleed onto the surface of the resin molded body to exert their effect, but when used for many years, they disappear due to wind and rain, and their effect does not last. In addition, when applied to the surface, there is a problem that the antistatic properties are insufficient and the antistatic properties disappear due to surface wear, etc. Furthermore, in order to improve the durability of antistatic properties, a resin molded product using a polymeric antistatic agent has been developed (Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-169350 A [Patent Document 2] JP 2014-105284 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the resin molded products using these conventional antistatic agents are not necessarily sufficient in terms of antistatic performance and its durability, and further improvements are currently desired. In addition, depending on the antistatic agent used, there is a problem that the wood texture of the molded product is impaired, and even when a large amount of the antistatic agent is used to exert sufficient antistatic properties, there is a problem that the wood texture of the molded product is impaired. Therefore, an object of the present invention is to provide an antistatic resin composition capable of providing a molded article having an excellent wood-like texture and excellent antistatic properties and their durability, and to provide a molded article having an excellent wood-like texture and excellent antistatic properties and their durability. [Means for solving the problem]

[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by providing the following configuration, and have thus completed the present invention. That is, the antistatic resin composition of the present invention is an antistatic resin composition containing, relative to 100 parts by mass of a polyolefin resin, 1 to 200 parts by mass of the following component (X), 1 to 60 parts by mass of the following component (Y), and 0.01 to 15.0 parts by mass of the following component (Z): (X) Ingredients: Wood flour. Component (Y): An antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Z): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

[0007] In the antistatic resin composition of the present invention, the polymer compound (E) is preferably obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.

[0008] In the antistatic resin composition of the present invention, it is preferable that the polymer compound (E) has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which the blocks are bonded via an ester bond or an ether bond formed by a reaction between a hydroxyl group or a carboxyl group at an end of the polyester (a), a hydroxyl group at an end of the polyether (b), and an epoxy group of the epoxy compound (D) or a hydroxyl group formed by a reaction of an epoxy group.

[0009] Furthermore, in the antistatic resin composition of the present invention, it is preferable that the polymer compound (E) has a structure in which the block polymer (C) having carboxyl groups at both ends and formed by repeatedly and alternately bonding the polyester block (A) and the polyether block (B) via ester bonds is bonded to the epoxy compound (D) via an ester bond.

[0010] In the antistatic resin composition of the present invention, the epoxy compound (D) of the polymer compound (E) is preferably polypropylene glycol diglycidyl ether. The present invention also provides a molded article obtained from the antistatic resin composition. Effect of the Invention

[0011] According to the present invention, it is possible to provide an antistatic resin composition capable of providing a molded article having an excellent wood-like texture and excellent antistatic properties and their durability, and to provide a molded article having an excellent wood-like texture and excellent antistatic properties and their durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described in detail. First, the antistatic resin composition of the present invention will be described. The resin composition of the present invention contains 1 to 200 parts by mass of the following component (X), 1 to 60 parts by mass of the following component (Y), and 0.01 to 15.0 parts by mass of the following component (Z) relative to 100 parts by mass of a polyolefin resin. (X) Ingredient: Wood flour Component (Y): An antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Z): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

[0013] First, the polyolefin resin used in the present invention will be described. Examples of polyolefin resins include low-density polyethylene, linear low-density polyethylene, high-density polyethylene, homopolypropylene, random copolymer polypropylene, impact copolymer polypropylene, block copolymer polypropylene, isotactic polypropylene, syndiotactic polypropylene, hemiisotactic polypropylene, polybutene, cycloolefin polymer, stereoblock polypropylene, α-olefin polymers such as poly-3-methyl-1-butene, poly-3-methyl-1-pentene, and poly-4-methyl-1-pentene, block or random copolymers of ethylene-propylene, α-olefin copolymers such as ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-vinyl acetate copolymer, and further polyolefin thermoplastic elastomers, and copolymers of two or more of these may be used. Two or more of these polyolefin resins may be used. As the polyolefin resin, polyethylene resins such as low-density polyethylene, linear low-density polyethylene, and high-density polyethylene are preferred from the viewpoints of antistatic property and its durability, and wood-like texture of the molded product.

[0014] Next, the wood flour as component (X) of the present invention will be described. In the antistatic resin composition of the present invention, wood flour is used as component (X). The average particle size of the wood flour is preferably 30 to 500 μm, more preferably 100 to 200 μm. If the average particle size is less than 30 μm, the bulk density of the wood flour becomes small and the mixability with polyolefin resin and other compounds tends to be poor, while if it exceeds 500 μm, the surface condition of the molded product tends to be poor, which is not preferable. The type of wood used for the wood flour is not particularly limited, and examples thereof include wood flour obtained from conifers such as cedar, lauan, Japanese larch, cypress, pine, and fir, and broad-leaved trees such as beech, birch, zelkova, boxwood, katsura, chestnut, cherry, and oak. In addition, finely ground sawdust, rice husks, and surface polishing powder of particle boards can also be used. The method for making the wood flour into fine powder is not particularly limited, and examples thereof include a method of finely grinding chipped wood with a dry grinder. The content of the (X) component in the resin composition is 1 to 200 parts by mass relative to 100 parts by mass of the polyolefin resin. From the viewpoints of antistatic property and its durability, and the woody texture of the molded product, the content is preferably 5 to 150 parts by mass, and more preferably 10 to 100 parts by mass.

[0015] Next, the component (Y) used in the present invention will be described. The component (Y) of the present invention is an antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and polytetramethylene glycol (b2).

[0016] In terms of the antistatic property and its durability, and the woody texture of the molded product, the polymer compound (E) related to this antistatic agent is preferably a polymer compound obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups. Furthermore, in terms of antistatic properties and their durability, and the woody texture of the molded product, the polymer compound (E) preferably has a structure in which a polyester block (A) composed of polyester (a) and a polyether block (B) composed of polyether (b) having hydroxyl groups at both ends are bonded via an ester bond or ether bond formed by the reaction of a hydroxyl group or carboxyl group at the end of polyester (a), a hydroxyl group at the end of polyether (b), and an epoxy group of epoxy compound (D) having two or more epoxy groups, or a hydroxyl group formed by the reaction of an epoxy group. Here, the hydroxyl group formed by the reaction of an epoxy group is a hydroxyl group formed by the ring-opening reaction of an epoxy group of epoxy compound (D) with a hydroxyl group or a carboxyl group.

[0017] The polyester block (A) of the polymer compound (E) is composed of a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2). The polyester (a) can be obtained by esterification of the diol (a1) with the dicarboxylic acid (a2). The diol (a1) used in the polymer compound (E) according to the present invention includes an aliphatic diol and an aromatic group-containing diol. The diol (a1) may be a mixture of two or more kinds.

[0018] Examples of aliphatic diols include 1,2-ethanediol (ethylene glycol), 1,2-propanediol (propylene glycol), 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2,2-diethyl-1,3-propanediol (3,3-dimethylol pentane), 2-n-butyl-2-ethyl-1,3propanediol (3,3-dimethylol heptane), 3-methyl 1,5-pentanediol, 1,6-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-octadecanediol, 1,4-cyclohexanedimethanol, hydrogenated bisphenol A, 1,2-, 1,3- or 1,4-cyclohexanediol, cyclododecanediol, dimer diol, hydrogenated dimer diol, diethylene glycol, dipropylene glycol, triethylene glycol, etc. Among these aliphatic diols, 1,4-cyclohexanedimethanol and hydrogenated bisphenol A are preferred from the viewpoints of antistatic properties and their durability, and the woody texture of the molded product, and 1,4-cyclohexanedimethanol is more preferred. In addition, it is preferable that the aliphatic diol has hydrophobic properties from the viewpoints of antistatic properties and their durability, and the wood-like texture of the molded article, so that the use of polyethylene glycol, which has hydrophilic properties, is not preferable.

[0019] Examples of aromatic group-containing diols include bisphenol A, 1,2-hydroxybenzene, 1,3-hydroxybenzene, 1,4-hydroxybenzene, 1,4-benzenedimethanol, ethylene oxide adduct of bisphenol A, propylene oxide adduct of bisphenol A, 1,4-bis(2-hydroxyethoxy)benzene, resorcin, polyhydroxyethyl adduct of mononuclear dihydric phenol compounds such as pyrocatechol, etc. Among these diols having aromatic groups, ethylene oxide adduct of bisphenol A and 1,4-bis(β-hydroxyethoxy)benzene are preferred. It is to be noted that aromatic diols are preferably hydrophobic in terms of antistatic properties and their durability, and woody texture of molded products. Among these diols, 1,4-cyclohexanedimethanol is particularly preferred from the viewpoints of antistatic properties and their durability, and the woody texture of the molded article.

[0020] The dicarboxylic acid (a2) used in the polymer compound (E) according to the present invention includes an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid. The dicarboxylic acid (a2) may be a mixture of two or more kinds.

[0021] The aliphatic dicarboxylic acid used in the polymer compound (E) according to the present invention may be a derivative of an aliphatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.). The aliphatic dicarboxylic acid and its derivative may be a mixture of two or more kinds. The aliphatic dicarboxylic acid preferably includes an aliphatic dicarboxylic acid having 2 to 20 carbon atoms, and examples thereof include oxalic acid, malonic acid, glutaric acid, methylsuccinic acid, dimethylmalonic acid, 3-methylglutaric acid, ethylsuccinic acid, isopropylmalonic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid (1,10-decanedicarboxylic acid), tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanediic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanediacetic acid, 1,3-cyclohexanediacetic acid, 1,2-cyclohexanediacetic acid, 1,1-cyclohexanediacetic acid, dimer acid, maleic acid, and fumaric acid. Among these aliphatic dicarboxylic acids, from the viewpoints of antistatic property and its durability, and the woody texture of the molded product, dicarboxylic acids having 4 to 12 carbon atoms are more preferred, and adipic acid is even more preferred.

[0022] The aromatic dicarboxylic acid used in the polymer compound (E) according to the present invention may be a derivative of an aromatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.). The aromatic dicarboxylic acid and its derivative may be a mixture of two or more kinds. The aromatic dicarboxylic acid is preferably an aromatic dicarboxylic acid having 8 to 20 carbon atoms, such as terephthalic acid, isophthalic acid, phthalic acid, phenylmalonic acid, homophthalic acid, phenylsuccinic acid, β-phenylglutaric acid, α-phenyladipic acid, β-phenyladipic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, naphthalenedicarboxylic acid, sodium 3-sulfoisophthalate, potassium 3-sulfoisophthalate, etc. Among these aromatic dicarboxylic acids, terephthalic acid, isophthalic acid, and phthalic acid (including phthalic anhydride) are preferred, and phthalic acid (including phthalic anhydride) is more preferred, from the viewpoints of antistatic properties and their durability, and the woody texture of the molded product. As the dicarboxylic acid (a2), it is preferable to use both an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid in combination, and it is particularly preferable to use adipic acid as the aliphatic dicarboxylic acid and phthalic acid (including phthalic anhydride) as the aromatic dicarboxylic acid in combination.

[0023] Next, the polyether (b) having hydroxyl groups at both ends and the polyether block (B) of the polymer compound (E) will be described. The polyether block (B) is composed of the polyether (b) having hydroxyl groups at both ends, and the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of the polytetramethylene glycol (b2) is 10 to 80 mol% based on the total number of moles of the polyethylene glycol (b1) and the polytetramethylene glycol (b2).

[0024] The number average molecular weight of the polyethylene glycol (b1) is calculated from the measured hydroxyl value, and from the viewpoints of antistatic property and its durability, and woody texture of the molded article, it is preferably 400 to 8,000, more preferably 1,000 to 6,000, even more preferably 1,500 to 5,000, and even more preferably 1,800 to 4,000. The method for measuring the hydroxyl value and the method for calculating the number average molecular weight from the hydroxyl value are described below.

[0025] <Calculation method of number average molecular weight from hydroxyl value> The hydroxyl value was measured by the following hydroxyl value measurement method, and the number average molecular weight (hereinafter also referred to as "Mn") was determined by the following formula. Number average molecular weight = (56110 x 2) / hydroxyl value

[0026] <Hydroxyl value measurement method> Reagent A (acetylating agent) (1) Triethyl phosphate 1560mL (2) Acetic anhydride 193 mL (3) Perchloric acid (60%) 16g Mix the above reagents in the order of (1) → (2) → (3). Reagent B Mix pyridine and pure water in a volume ratio of 3:1. Reagent C Add 2 to 3 drops of phenolphthalein solution to 500 mL of isopropyl alcohol and neutralize with 1N KOH aqueous solution. First, weigh out 2 g of sample into a 200 mL Erlenmeyer flask, add 10 mL of xylene, and heat to dissolve. Add 15 mL of Reagent A, plug with a stopper, and shake vigorously. Add 20 mL of Reagent B, plug with a stopper, and shake vigorously. Add 50 mL of Reagent C. Titrate with 1N KOH aqueous solution and calculate using the formula below. Hydroxyl value [mgKOH / g] = 56.11 × f × (TB) / S f: Factor of 1N-KOH solution B: Blank test titration volume [mL] T: Test titer [mL] S: Sample amount [g]

[0027] The number average molecular weight of the polytetramethylene glycol (b2) is calculated from the measured hydroxyl value, and from the viewpoints of antistatic property and its durability, and the woody texture of the molded product, it is preferably 400 to 8,000, more preferably 1,000 to 6,000, even more preferably 1,500 to 5,000, and even more preferably 1,800 to 4,000. The method for measuring the hydroxyl value of polytetramethylene glycol (b2) and the method for calculating the number average molecular weight from the hydroxyl value are the same as the method for measuring the hydroxyl value of polyethylene glycol (a1) and the method for calculating the number average molecular weight from the hydroxyl value. The ratio of polyethylene glycol (b1) and polytetramethylene glycol (b2) in the polyether (b) having hydroxyl groups at both ends is 10 to 80 mol % of polytetramethylene glycol (b2) relative to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). From the viewpoints of antistatic property and its durability, and the woody texture of the molded product, the ratio is preferably 15 to 70 mol %, more preferably 18 to 55 mol %, and even more preferably 20 to 50 mol %.

[0028] Next, the epoxy compound (D) having two or more epoxy groups constituting the polymer compound (E) will be described. The epoxy compound (D) used in the antistatic agent of the present invention is not particularly limited as long as it has two or more epoxy groups, and examples thereof include polyglycidyl ether compounds of mononuclear polyhydric phenol compounds such as hydroquinone, resorcin, pyrocatechol, and phloroglucinol; dihydroxynaphthalene, biphenol, methylene bisphenol (bisphenol F), methylene bis(ortho-cresol), ethylidene bisphenol, isopropylidene bisphenol (bisphenol A), isopropylidene bis(ortho-cresol), tetrabromobisphenol, and the like. Polyglyceryl esters of polynuclear polyhydric phenol compounds such as phenol A, 1,3-bis(4-hydroxycumylbenzene), 1,4-bis(4-hydroxycumylbenzene), 1,1,3-tris(4-hydroxyphenyl)butane, 1,1,2,2-tetra(4-hydroxyphenyl)ethane, thiobisphenol, sulfobisphenol, oxybisphenol, phenol novolac, orthocresol novolac, ethylphenol novolac, butylphenol novolac, octylphenol novolac, resorcinol novolac, and terpene phenol. ether compounds; polyglycidyl ethers of polyhydric alcohols such as ethylene glycol, propylene glycol, butylene glycol, hexanediol, diethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, polyglycol, thiodiglycol, glycerin, trimethylolpropane, pentaerythritol, sorbitol, bisphenol A-ethylene oxide adduct, and dicyclopentadiene dimethanol; maleic acid, fumaric acid, itaconic acid, succinic acid, glutaric acid, suberic acid, adipic acid, Homopolymers or copolymers of glycidyl esters of aliphatic, aromatic or alicyclic polybasic acids, such as azelaic acid, sebacic acid, dimer acid, trimer acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, tetrahydrophthalic acid, hexahydrophthalic acid, endomethylenetetrahydrophthalic acid, and glycidyl methacrylate; epoxy compounds having a glycidylamino group, such as N,N-diglycidylaniline, bis(4-(N-methyl-N-glycidylamino)phenyl)methane, and diglycidyl orthotoluidine;Examples of epoxy compounds include cyclic olefin compounds such as vinylcyclohexene diepoxide, dicyclopentadiene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-6-methylcyclohexane carboxylate, and bis(3,4-epoxy-6-methylcyclohexylmethyl) adipate; epoxidized conjugated diene polymers such as epoxidized polybutadiene and epoxidized styrene-butadiene copolymers, heterocyclic compounds such as triglycidyl isocyanurate, and epoxidized soybean oil. These epoxy compounds may be internally crosslinked with a prepolymer of terminal isocyanate, or may be polymerized using a polyvalent active hydrogen compound (polyhydric phenol, polyamine, carbonyl group-containing compound, polyphosphate ester, etc.). Two or more of such epoxy compounds (D) may be used.;

[0029] From the viewpoints of antistatic property and its durability, and the wood texture of the molded article, the epoxy compound (D) is preferably polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, dicyclopentadiene dimethanol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, or hexanediol diglycidyl ether, more preferably polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, or hydrogenated bisphenol A diglycidyl ether, and even more preferably polypropylene glycol diglycidyl ether. From the viewpoints of antistatic property and its durability, and the wood texture of the molded article, the polypropylene glycol diglycidyl ether represented by the following general formula (1) is particularly preferred.

[0030] [ka]

[0031] In general formula (1), n ​​represents a number of 1 to 30. n is preferably 2 to 25, and more preferably 3 to 15, from the viewpoints of antistatic property and its durability, and the woody texture of the molded article. The number average molecular weight of the polypropylene glycol diglycidyl ether is preferably from 200 to 2,000, more preferably from 250 to 1,500, and even more preferably from 300 to 1,000, from the viewpoints of antistatic property and its durability, and woody texture of the molded article.

[0032] As the polypropylene glycol diglycidyl ether, a commercially available product may be used. Examples of commercially available products include ADEKA GLYCIROL (registered trademark) ED-506 manufactured by ADEKA CORPORATION, DENACOL (registered trademark) EX-920 and DENACOL (registered trademark) EX-931 manufactured by Nagase ChemteX Corporation, and the like. The epoxy equivalent of the epoxy compound (D) is preferably from 70 to 2000, more preferably from 100 to 1000, particularly preferably from 150 to 600, from the viewpoints of antistatic property and its durability, and woody texture of the molded product.

[0033] In terms of the present invention, from the viewpoints of antistatic properties and their durability, and the wood-like texture of the molded article, a preferred polymer compound (E) is one obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), with a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, and has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which the hydroxyl or carboxyl group at the end of the polyester (a) is bonded via an ester bond or an ether bond formed by the reaction of the hydroxyl group at the end of the polyether (b) with the epoxy group of an epoxy compound having two or more epoxy groups, or the hydroxyl group formed by the reaction of this epoxy group, is preferred in terms of the antistatic properties and their durability, and the wood-like texture of the molded article.

[0034] Furthermore, from the viewpoints of antistatic properties and their durability, and the wood-like texture of the molded product, the polymer compound (E) preferably has a structure in which a block polymer (C) having carboxyl groups at both ends, which is formed by repeatedly and alternately bonding a polyester block (A) composed of a polyester (a) and a polyether block (B) composed of a polyether (b) via ester bonds, is bonded to an epoxy compound (D) via an ester bond formed by the carboxyl group of the block polymer (C) and the epoxy group of the epoxy compound (D). It is also preferable that the polymer compound (E) has a structure in which a hydroxyl group formed by ring-opening of the epoxy group in a reaction with the carboxyl group is bonded to the carboxyl group via an ester bond formed by the reaction with the carboxyl group.

[0035] The polyester (a) constituting the block of the polyester (A) according to the present invention may be any one that is composed of a diol (a1) and a dicarboxylic acid (a2), and preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol (a1) and the residue obtained by removing the carboxyl group of the dicarboxylic acid (a2) are bonded via an ester bond from the viewpoints of antistatic properties and their duration and the woody feel of the molded article. A more preferred polyester (a) constituting the block (A) of the polyester according to the present invention is one that is composed of a diol, an aliphatic dicarboxylic acid, and an aromatic dicarboxylic acid, and preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol and the residue obtained by removing the carboxyl group of the aliphatic dicarboxylic acid are bonded via an ester bond from the viewpoints of antistatic properties and their duration and the woody feel of the molded article, and further preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol and the residue obtained by removing the carboxyl group of the aromatic dicarboxylic acid are bonded via an ester bond from the viewpoints of antistatic properties and their duration and the woody feel of the molded article.

[0036] In addition, the polyester (a) preferably has a structure having carboxyl groups at both ends in terms of antistatic properties and their durability, and the wood-like texture of the molded product. Furthermore, the polymerization degree of the polyester (a) is preferably in the range of 2 to 50 in terms of antistatic properties and their durability, and the wood-like texture of the molded product. The polyester (a) having carboxyl groups at both ends can be obtained, for example, by esterification reaction of the above diol (a1) with the above dicarboxylic acid (a2) (preferably an aliphatic dicarboxylic acid or an aromatic dicarboxylic acid).

[0037] The aliphatic dicarboxylic acid may be a derivative of an aliphatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.), and when a derivative is used to obtain polyester (a), both ends may be finally treated to give carboxyl groups, or the polyester may be directly subjected to the next reaction to obtain block polymer (C) having a structure having carboxyl groups at both ends. The aliphatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.

[0038] The aromatic dicarboxylic acid may be a derivative of an aromatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.), and when a polyester is obtained using a derivative, both ends are finally treated to form carboxyl groups, and the polyester may be directly subjected to the next reaction for obtaining a block polymer (C) having a structure having carboxyl groups at both ends. The aromatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.

[0039] When an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid are used, the molar ratio of the residues of the aliphatic dicarboxylic acid excluding the carboxyl groups to the residues of the aromatic dicarboxylic acid excluding the carboxyl groups in the polyester (a) is preferably 90:10 to 99.9:0.1, and more preferably 93:7 to 99.9:0.1, from the viewpoints of antistatic property and its durability, and the woody texture of the molded product.

[0040] The polyester (a) having carboxyl groups at both ends can be obtained, for example, by esterification reaction of the above-mentioned dicarboxylic acid or its derivative (preferably the above-mentioned aliphatic dicarboxylic acid or its derivative, and the above-mentioned aromatic dicarboxylic acid or its derivative) with the above-mentioned diol. Regarding the reaction ratio of dicarboxylic acid or derivative thereof (preferably, an aliphatic dicarboxylic acid or derivative thereof, and an aromatic dicarboxylic acid or derivative thereof) to diol, it is preferable to use an excess of dicarboxylic acid or derivative thereof (preferably, an aliphatic dicarboxylic acid or derivative thereof, and an aromatic dicarboxylic acid or derivative thereof) so that both ends have carboxyl groups, and it is preferable to use one mole excess relative to the diol in terms of molar ratio. The compounding ratio of the aliphatic dicarboxylic acid or its derivative to the aromatic dicarboxylic acid or its derivative during the esterification reaction is preferably from 90:10 to 99.9:0.1, more preferably from 93:7 to 99.9:0.1, in terms of molar ratio.

[0041] Depending on the compounding ratio and reaction conditions, a polyester composed only of a diol and an aliphatic dicarboxylic acid or a polyester composed only of a diol and an aromatic dicarboxylic acid may be produced. In the present invention, however, these may be mixed into the polyester (a) and may be reacted as they are with the compound (b) to obtain the block polymer (C). The esterification reaction may be carried out in the presence of a catalyst for accelerating the reaction. As the catalyst, a conventional catalyst such as dibutyltin oxide, tetraalkyl titanate, zirconium acetate, zinc acetate, etc. may be used.

[0042] In addition, when a derivative of a dicarboxylic acid (preferably an aliphatic dicarboxylic acid or an aromatic dicarboxylic acid) such as a carboxylate, a carboxylate metal salt, or a carboxylate halide is used instead of a dicarboxylic acid, the dicarboxylic acid may be reacted with a diol and then treated at both ends to give a dicarboxylic acid, or the dicarboxylic acid may be directly subjected to the next reaction for obtaining a block polymer (C) having a structure having carboxyl groups at both ends.

[0043] A suitable polyester (a) consisting of a diol and a dicarboxylic acid (preferably an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid) and having carboxyl groups at both ends may be any polyester that reacts with a polyether (b) to form an ester bond and form a block polymer (C) structure, and the carboxyl groups at both ends may be protected or modified, or may be in the form of a precursor. In order to suppress oxidation of the product during the reaction, an antioxidant such as a phenol-based antioxidant may be added to the reaction system.

[0044] The polyether (b) having hydroxyl groups at both ends preferably reacts with the polyester (a) to form an ester bond or an ether bond, preferably an ester bond, to form a block polymer (C) structure. The hydroxyl groups at both ends may be protected or modified, or may be in the form of a precursor.

[0045] The block polymer (C) having a structure having carboxyl groups at both ends of the polymer compound (E) according to the present invention has a structure in which the block (A) composed of the above polyester (a) and the block (B) composed of the above polyether (b) are repeatedly and alternately bonded via ester bonds formed by carboxyl groups and hydroxyl groups. An example of such a block polymer (C) is one having a structure represented by the following general formula (2).

[0046] [ka]

[0047] In general formula (2), (A) represents a block composed of the polyester (a) having carboxyl groups at both ends, (B) represents a block composed of the polyether (b) having hydroxyl groups at both ends, and t represents the number of repeating units, which is preferably a number from 1 to 10 in terms of antistatic properties and their durability, and the woody texture of the molded product. t is more preferably a number from 1 to 7, and most preferably a number from 1 to 5.

[0048] The block polymer (C) having a structure having carboxyl groups at both ends can be obtained by polycondensation reaction of a polyester (a) having carboxyl groups at both ends and a polyether (b) having hydroxyl groups at both ends. However, it is not necessary to synthesize the block polymer (C) from the polyester (a) and the polyether (b) as long as the block polymer (C) has a structure equivalent to a structure in which the polyester (a) and the polyether (b) are repeatedly and alternately bonded via ester bonds formed by a carboxyl group and a hydroxyl group.

[0049] The reaction ratio of the polyester (a) to the polyether (b) is adjusted so that the amount of the polyester (a) is X+1 moles per mole of the polyether (b), thereby making it possible to preferably obtain a block polymer (C) having carboxyl groups at both ends. In the reaction, after completion of the synthesis reaction of the polyester (a), the polyester (a) may not be isolated, but the polyether (b) may be added to the reaction system and reacted as is.

[0050] In the polycondensation reaction, a catalyst for promoting the esterification reaction may be used, and as the catalyst, a conventionally known catalyst such as dibutyltin oxide, tetraalkyl titanate, zirconium acetate, zinc acetate, etc. In order to suppress oxidation of the product during the reaction, an antioxidant such as a phenol-based antioxidant may be added to the reaction system.

[0051] From the viewpoints of antistatic properties and their durability, and the woody texture of the molded article, the polymer compound (E) according to the present invention preferably has a structure in which a block polymer (C) having a structure with carboxyl groups at both ends and an epoxy compound (D) having two or more epoxy groups are bonded via an ester bond. The ester bond may be either an ester bond formed by the reaction of a carboxyl group at the end of the block polymer (C) with an epoxy group of the epoxy compound (D), or an ester bond formed by the reaction of a hydroxyl group formed by this reaction (a reaction of a carboxyl group with an epoxy group) with a carboxyl group, and it is preferable that both ester bonds are present from the viewpoints of antistatic properties and their durability, and the woody texture of the molded article. Moreover, the polymer compound (E) may further contain an ester bond formed between a carboxyl group of the polyester (a) and an epoxy group of the epoxy compound (D).

[0052] Furthermore, the polymer compound (E) may contain an ester bond formed between a carboxyl group of the polyester (a) and a hydroxyl group formed by reaction of an epoxy group of the epoxy compound. Furthermore, the polymer compound (E) may further contain an ether bond formed by a hydroxyl group of the polyester (a) or a hydroxyl group of the polyether (b) and an epoxy group of the epoxy compound (D).

[0053] In order to obtain a preferred polymer compound (E), the block polymer (C) and the epoxy compound (D) may be reacted. That is, the carboxyl group of the block polymer (C) may be reacted with the epoxy group of the epoxy compound (D). More preferably, the hydroxyl group formed from the reacted epoxy group may be reacted with the carboxyl group. The number of epoxy groups in the epoxy compound (D) is preferably 0.5 to 5 equivalents, more preferably 0.5 to 1.5 equivalents, of the number of carboxyl groups in the block polymer (C) to be reacted. The reaction may be carried out in various solvents or in a molten state. The amount of the epoxy compound (D) having two or more epoxy groups to be reacted is preferably 0.1 to 2.0 equivalents, more preferably 0.2 to 1.5 equivalents, relative to the number of carboxyl groups in the block polymer (C) to be reacted.

[0054] In the reaction, after completion of the synthesis reaction of the block polymer (C), the epoxy compound (D) may be added to the reaction system and reacted as it is without isolating the block polymer (C). In this case, the carboxyl groups of the unreacted polyester (a) used in excess when synthesizing the block polymer (C) may react with some of the epoxy groups of the epoxy compound (D) to form ester bonds.

[0055] A preferred polymer compound (E) according to the present invention does not necessarily have to be synthesized from the block polymer (C) and the epoxy compound (D) as long as it has a structure equivalent to that of a block polymer (C) having a structure with carboxyl groups at both ends and an epoxy compound (D) having two or more epoxy groups bonded via an ester bond formed between the respective carboxyl groups and epoxy groups. The ester bond formed between a carboxyl group and an epoxy group as referred to here also includes an ester bond formed between a carboxyl group and a hydroxyl group formed from an epoxy group by reacting with the carboxyl group.

[0056] In addition, the polymer compound (E) according to the present invention may be prepared by obtaining a polyester (a) from a diol (a1) and a dicarboxylic acid (a2), and then reacting the polyester (a) with a polyether (b) and / or an epoxy compound (D) without isolating the polyester (a). In the polymer compound (E) of the present invention, the number average molecular weight of the polyester (a) constituting the block (A) composed of the polyester (a) is, in terms of polystyrene, preferably 1,000 to 10,000, more preferably 1,500 to 8,000, and even more preferably 2,500 to 7,500, from the viewpoints of antistatic property and its durability, and woody texture of the molded product. If the number average molecular weight is less than 1,000, the storage stability may be poor, and if it exceeds 10,000, the reaction to obtain the polymer compound (E) may take a long time, which may result in poor economic efficiency, or the obtained polymer compound may become discolored due to the long reaction time. The method for measuring the number average molecular weight in terms of polystyrene is preferably gel permeation chromatography (GPC), and the measuring method is shown below.

[0057] <Method for measuring number average molecular weight based on polystyrene conversion> The number average molecular weight (hereinafter also referred to as "Mn") was measured by gel permeation chromatography (GPC). The measurement conditions for Mn were as follows: Equipment: GPC equipment manufactured by JASCO Corporation Solvent: Chloroform Reference material: Polystyrene Detector: Differential refractometer (RI detector) Column stationary phase: Showa Denko Shodex LF-804 Column temperature: 40℃ Sample concentration: 1mg / 1mL Flow rate: 0.8mL / min. Injection volume: 100μL

[0058] Furthermore, the number average molecular weight of the block polymer (C) having a structure with carboxyl groups at both ends in the polymer compound (E) is preferably 5,000 to 50,000, more preferably 10,000 to 45,000, in terms of antistatic properties and their durability, and the woody texture of the molded product, in terms of polystyrene. If the number average molecular weight is less than 5,000, the storage stability may be poor, and if it exceeds 50,000, the reaction to obtain the polymer compound (E) may take a long time, which may result in poor economic efficiency, or the obtained polymer compound may become discolored due to a long reaction time. The method for measuring the number average molecular weight in terms of polystyrene is preferably gel permeation chromatography (GPC), and the measuring method is as described above. In the antistatic resin composition of the present invention, the content of the (Y) component is 1 to 60 parts by mass relative to 100 parts by mass of the polyolefin resin. From the viewpoints of antistatic property and its durability, and the woody texture of the molded product, the content is preferably 5 to 50 parts by mass, and more preferably 10 to 40 parts by mass.

[0059] Next, the component (Z) of the present invention will be described. The component (Z) of the present invention is one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

[0060] Hereinafter, the alkali metal salt (F) will be described first. Examples of the alkali metal salt (F) include salts of organic acids or inorganic acids, and examples of the alkali metal include lithium, sodium, potassium, cesium, and rubidium. Examples of the organic acid include aliphatic monocarboxylic acids having 1 to 18 carbon atoms, such as formic acid, acetic acid, propionic acid, butyric acid, and lactic acid; aliphatic dicarboxylic acids having 1 to 12 carbon atoms, such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, and salicylic acid; and sulfonic acids having 1 to 20 carbon atoms, such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and trifluoromethanesulfonic acid. Examples of the inorganic acid include hydrochloric acid, hydrobromic acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, polyphosphoric acid, nitric acid, and perchloric acid. Among them, in terms of antistatic property and its duration, woody texture of the molded product, and safety to living organisms and the environment, lithium, sodium, and potassium salts are preferred, and sodium is more preferred. In terms of antistatic property and its duration, and woody texture of the molded product, acetic acid salts, perchloric acid salts, p-toluenesulfonic acid salts, and dodecylbenzenesulfonic acid salts are preferred, and dodecylbenzenesulfonic acid salts are more preferred. Two or more kinds of alkali metal salts may be used.

[0061] Specific examples of the alkali metal salt (F) include lithium acetate, sodium acetate, potassium acetate, lithium chloride, sodium chloride, potassium chloride, lithium phosphate, sodium phosphate, potassium phosphate, lithium sulfate, sodium sulfate, lithium perchlorate, sodium perchlorate, potassium perchlorate, lithium p-toluenesulfonate, sodium p-toluenesulfonate, potassium p-toluenesulfonate, lithium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, etc. Among these, in terms of antistatic properties and their durability, the woody texture of the molded product, and safety to living organisms and the environment, preferred are lithium p-toluenesulfonate, sodium p-toluenesulfonate, lithium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, etc., and most preferred is sodium dodecylbenzenesulfonate.

[0062] Next, the ionic liquid (G) will be described. Examples of ionic liquids include room-temperature molten salts having a melting point of 100°C or less, at least one of the cations or anions constituting the ionic liquid being an organic ion, and having an initial conductivity of 1 to 200 ms / cm, preferably 10 to 200 ms / cm, such as those described in WO 95 / 15572. Examples of the cations constituting the ionic liquid include cations selected from the group consisting of amidinium, pyridinium, pyrazolium and guanidinium cations. Among these, examples of the amidinium cation include the following:

[0063] (1) Imidazolinium cation Examples of the imidazolinium include those having 5 to 15 carbon atoms, such as 1,2,3,4-tetramethylimidazolinium and 1,3-dimethylimidazolinium; (2) Imidazolium cation Examples of the imidazolium derivatives include those having 5 to 15 carbon atoms, such as 1,3-dimethylimidazolium and 1-ethyl-3-methylimidazolium; (3) Tetrahydropyrimidinium cation Examples of the aryl group include those having 6 to 15 carbon atoms, such as 1,3-dimethyl-1,4,5,6-tetrahydropyrimidinium and 1,2,3,4-tetramethyl-1,4,5,6-tetrahydropyrimidinium; (4) Dihydropyrimidinium cation Examples of the alkyl group include those having 6 to 20 carbon atoms, such as 1,3-dimethyl-1,4-dihydropyrimidinium, 1,3-dimethyl-1,6-dihydropyrimidinium, 8-methyl-1,8-diazabicyclo[5,4,0]-7,9-undecadienium, and 8-methyl-1,8-diazabicyclo[5,4,0]-7,10-undecadienium.

[0064] The pyridinium cation may be one having 6 to 20 carbon atoms, such as 3-methyl-1-propylpyridinium and 1-butyl-3,4-dimethylpyridinium. The pyrazolium cation may be one having 5 to 15 carbon atoms, such as 1,2-dimethylpyrazolium or 1-n-butyl-2-methylpyrazolium.

[0065] The guanidinium cations include the following: (1) Guanidinium cation with an imidazolinium skeleton Examples of the imidazolium salt include those having 8 to 15 carbon atoms, such as 2-dimethylamino-1,3,4-trimethylimidazolinium and 2-diethylamino-1,3,4-trimethylimidazolinium; (2) Guanidinium cation with an imidazolium skeleton Examples of the imidazolium derivatives include those having 8 to 15 carbon atoms, such as 2-dimethylamino-1,3,4-trimethylimidazolium and 2-diethylamino-1,3,4-trimethylimidazolium; (3) Guanidinium cation having a tetrahydropyrimidinium skeleton Examples of the alkyl group include those having 10 to 20 carbon atoms, such as 2-dimethylamino-1,3,4-trimethyl-1,4,5,6-tetrahydropyrimidinium and 2-diethylamino-1,3-dimethyl-4-ethyl-1,4,5,6-tetrahydropyrimidinium; (4) Guanidinium cation having a dihydropyrimidinium skeleton Examples thereof include those having 10 to 20 carbon atoms, such as 2-dimethylamino-1,3,4-trimethyl-1,4-dihydropyrimidinium, 2-dimethylamino-1,3,4-trimethyl-1,6-dihydropyrimidinium, 2-diethylamino-1,3-dimethyl-4-ethyl-1,4-dihydropyrimidinium, and 2-diethylamino-1,3-dimethyl-4-ethyl-1,6-dihydropyrimidinium.

[0066] The above cations may be used alone or in combination of two or more. Among these, from the viewpoints of antistatic property and its durability, and woody texture of the molded article, the amidinium cation is preferred, the imidazolium cation is more preferred, and the 1-ethyl-3-methylimidazolium cation is particularly preferred.

[0067] In the ionic liquid, examples of organic or inorganic acids constituting the anion include the following. Examples of organic acids include carboxylic acids, sulfuric esters, sulfonic acids, and phosphoric esters; examples of inorganic acids include superacids (e.g., borofluoroacid, tetrafluoroboric acid, perchloric acid, hexafluorophosphoric acid, hexafluoroantimonic acid, and hexafluoroarsenic acid), phosphoric acid, and boric acid. The above organic acids and inorganic acids may be used alone or in combination of two or more.

[0068] Among the above organic acids and inorganic acids, the ionic liquid is preferable in terms of the antistatic property and its durability, and the woody texture of the molded product. 0 ) is 12 to 100, conjugate bases of superacids, acids that form anions other than the conjugate bases of superacids, and mixtures thereof.

[0069] Examples of anions other than the conjugate base of a superacid include halogen (e.g., fluorine, chlorine, and bromine) ions, alkyl (having 1 to 12 carbon atoms) benzenesulfonic acid (e.g., p-toluenesulfonic acid and dodecylbenzenesulfonic acid) ions, and poly(n=1 to 25) fluoroalkanesulfonic acid (e.g., undecafluoropentanesulfonic acid) ions.

[0070] In addition, examples of the super strong acid include protonic acids and those derived from a combination of a protonic acid and a Lewis acid, and mixtures thereof. Examples of the protonic acid as the super strong acid include bis(trifluoromethylsulfonyl)imide acid, bis(pentafluoroethylsulfonyl)imide acid, tris(trifluoromethylsulfonyl)methane, perchloric acid, fluorosulfonic acid, alkane (having 1 to 30 carbon atoms)sulfonic acid (e.g., methanesulfonic acid, dodecanesulfonic acid, etc.), poly(n=1 to 30)fluoroalkane (having 1 to 30 carbon atoms)sulfonic acid (e.g., trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoropropanesulfonic acid, nonafluorobutanesulfonic acid, undecafluoropentanesulfonic acid, and tridecafluorohexanesulfonic acid), borofluoric acid, and tetrafluoroboric acid. Among these, preferred from the viewpoint of ease of synthesis are borofluoroacid, trifluoromethanesulfonic acid, bis(trifluoromethanesulfonyl)imidic acid and bis(pentafluoroethylsulfonyl)imidic acid. Examples of protonic acids used in combination with the Lewis acid include hydrogen halides (e.g., hydrogen fluoride, hydrogen chloride, hydrogen bromide, and hydrogen iodide), perchloric acid, fluorosulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, undecafluoropentanesulfonic acid, tridecafluorohexanesulfonic acid, and mixtures thereof. Among these, hydrogen fluoride is preferred from the viewpoint of the initial conductivity of the ionic liquid. Examples of Lewis acids include boron trifluoride, phosphorus pentafluoride, antimony pentafluoride, arsenic pentafluoride, tantalum pentafluoride, and mixtures thereof. Among these, boron trifluoride and phosphorus pentafluoride are preferred from the viewpoint of the initial conductivity of the ionic liquid.

[0071] The combination of the protonic acid and the Lewis acid is arbitrary, and examples of super strong acids formed by these combinations include tetrafluoroboric acid, hexafluorophosphoric acid, hexafluorotantalic acid, hexafluoroantimonic acid, hexafluorotantalum sulfonic acid, tetrafluoroboric acid, hexafluorophosphoric acid, chlorotrifluoroboric acid, hexafluoroarsenic acid, and mixtures thereof. Of the above anions, from the viewpoints of the antistatic properties and their durability of the ionic liquid and the wood-like texture of the molded body, preferred are the conjugate bases of super strong acids (super strong acids made of protonic acids and super strong acids made of a combination of a protonic acid and a Lewis acid), and more preferred are super strong acids made of protonic acids and conjugate bases of super strong acids made of a protonic acid, boron trifluoride and / or phosphorus pentafluoride.

[0072] Among ionic liquids, from the viewpoints of antistatic properties and their durability, and the wood-like texture of the molded article, preferred are ionic liquids having an amidinium cation, more preferred are ionic liquids having a 1-ethyl-3-methylimidazolium cation, and particularly preferred is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.

[0073] In the component (Z) of the present invention, the alkali metal salt (F) and the ionic liquid (G) may be used in combination. In the antistatic resin composition of the present invention, the content of the (Z) component is 0.01 to 15.0 parts by mass relative to 100 parts by mass of the polyolefin resin, and from the viewpoints of antistatic property and its durability, and the woody texture of the molded product, is more preferably 0.1 to 12.0 parts by mass, even more preferably 0.5 to 10.0 parts by mass, and even more preferably 1.0 to 8.0 parts by mass. When the (Z) component is blended with the polyolefin resin, it may be blended directly, or the (Z) component may be added to the reaction system during the synthesis reaction of the polymer compound (E) which is the (Y) component, and then blended.

[0074] The resin composition of the present invention preferably contains a compatibilizer in terms of antistatic properties and their durability, and the woody texture of the molded product. The compatibilizer may be one or more acid anhydride-modified polyolefins. The acid anhydride-modified polyolefin is a polymer in which an acid anhydride such as maleic anhydride is grafted onto a polyolefin.

[0075] The polyolefin portion of the acid anhydride modified polyolefin may be a polymer or copolymer of ethylene, propylene, α-olefin or diene, and examples of the α-olefin include 1-butene, 4-methyl-1-pentene, 1-pentene, 1-octene, 1-decene, 1-dodecene, etc., and examples of the diene include butadiene, isoprene, cyclopentadiene, 1,11-dodecadiene, etc. In addition to these, other copolymerization components may be included. More specifically, examples of the polyolefin include polyethylene, polypropylene, ethylene / propylene copolymer, ethylene / propylene / diene terpolymer, ethylene / 1-butene copolymer, ethylene / vinyl acetate copolymer, and mixtures thereof. Among these, from the viewpoints of antistatic properties and their durability, and the woody texture of the molded product, polymers or copolymers of ethylene, propylene, α-olefins having 4 to 12 carbon atoms, butadiene, and isoprene are preferred, polymers or copolymers of ethylene, propylene, α-olefins having 4 to 8 carbon atoms, and butadiene are more preferred, and polymers or copolymers of ethylene, propylene, and butadiene are even more preferred. Examples of the acid anhydride include maleic anhydride and itaconic anhydride, with maleic anhydride being preferred from the standpoint of antistatic properties and their durability, and the wood-like texture of the molded product. The acid anhydride-modified polyolefin is preferably a maleic anhydride-modified polyolefin, more preferably a maleic anhydride-modified polypropylene, from the viewpoints of antistatic property and its durability, and woody texture of the molded product. The acid anhydride-modified polyolefin is obtained by a grafting reaction of an acid anhydride such as maleic anhydride to a polyolefin by a conventionally known method, and various commercially available products may be used.

[0076] In the antistatic resin composition of the present invention, the content of the compatibilizer is preferably 0.01 to 30.0 parts by mass, more preferably 0.1 to 20.0 parts by mass, and even more preferably 0.5 to 15.0 parts by mass, relative to 100 parts by mass of the polyolefin resin, from the viewpoints of antistatic property and its durability, and the woody texture of the molded product.

[0077] The resin composition of the present invention may further contain a salt of a Group 2 element within a range that does not impair the effects of the present invention. Examples of salts of Group 2 elements include salts of organic acids or inorganic acids, and examples of Group 2 elements include beryllium, magnesium, calcium, strontium, barium, etc. Examples of organic acids include aliphatic monocarboxylic acids having 1 to 18 carbon atoms, such as formic acid, acetic acid, propionic acid, butyric acid, and lactic acid; aliphatic dicarboxylic acids having 1 to 12 carbon atoms, such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, and salicylic acid; and sulfonic acids having 1 to 20 carbon atoms, such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and trifluoromethanesulfonic acid. Examples of inorganic acids include hydrochloric acid, hydrobromic acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, polyphosphoric acid, nitric acid, and perchloric acid.

[0078] The resin composition of the present invention may contain a surfactant within a range that does not impair the effects of the present invention. As the surfactant, a nonionic, anionic, cationic or amphoteric surfactant can be used. Examples of the nonionic surfactant include polyethylene glycol-type nonionic surfactants such as higher alcohol ethylene oxide adducts, fatty acid ethylene oxide adducts, higher alkylamine ethylene oxide adducts, and polypropylene glycol ethylene oxide adducts; and polyhydric alcohol-type nonionic surfactants such as polyethylene oxide, fatty acid esters of glycerin, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol or sorbitan, alkyl ethers of polyhydric alcohols, and fatty amides of alkanolamines. Examples of the anionic surfactant include carboxylates such as alkali metal salts of higher fatty acids; sulfates such as higher alcohol sulfates and higher alkyl ether sulfates; sulfonates such as alkylbenzene sulfonates, alkyl sulfonates and paraffin sulfonates; and phosphates such as higher alcohol phosphates. Examples of the cationic surfactant include quaternary ammonium salts such as alkyltrimethylammonium salts. Examples of amphoteric surfactants include amino acid type amphoteric surfactants such as higher alkylaminopropionate salts, betaine type amphoteric surfactants such as higher alkyldimethylbetaine and higher alkyldihydroxyethylbetaine, and the like. These can be used alone or in combination of two or more kinds. When a surfactant is added, the amount added is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 2 parts by mass, based on 100 parts by mass of the polyolefin resin.

[0079] Furthermore, the resin composition of the present invention may contain a polymeric antistatic agent. For example, a known polymeric antistatic agent such as polyetheresteramide can be used as the polymeric antistatic agent. For example, a known polyetheresteramide can be used, which is a polyetheresteramide consisting of a polyoxyalkylene adduct of bisphenol A described in JP-A-7-10989. In addition, a block polymer having a repeating structure with 2 to 50 bond units between a polyolefin block and a hydrophilic polymer block can be used, which is an example of the block polymer described in U.S. Pat. No. 6,552,131. When a polymer-type antistatic agent is blended, the blending amount is preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the polyolefin resin.

[0080] Furthermore, various additives such as a phenol-based antioxidant, a phosphorus-based antioxidant, a thioether-based antioxidant, a hindered amine-based light stabilizer, and an ultraviolet absorber can be further added to the resin composition of the present invention within a range that does not impair the effects of the present invention, thereby stabilizing the resin composition of the present invention.

[0081] Examples of the phenol-based antioxidants include 2,6-di-tert-butyl-p-cresol, 2,6-diphenyl-4-octadecyloxyphenol, distearyl (3,5-di-tert-butyl-4-hydroxybenzyl)phosphonate, 1,6-hexamethylenebis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid amide], 4,4'-thiobis(6-tert-butyl-m-cresol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-butyl-m-cresol, ... 2,2'-ethylidenebis(6-tert-butyl-m-cresol), 2,2'-ethylidenebis(4,6-di-tert-butylphenol), 2,2'-ethylidenebis(4-sec-butyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, diethyl)-2,4,6-trimethylbenzene, 2-tert-butyl-4-methyl-6-(2-acryloyloxy-3-tert-butyl-5-methylbenzyl)phenol, stearyl (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate methyl]methane, thiodiethylene glycol bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,6-hexamethylene bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 〕, bis[3,3-bis(4-hydroxy-3-tert-butylphenyl)butyric acid]glycol ester, bis[2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl]terephthalate, 1,3,5-tris[(3,5-ditert-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate, 3,9-bis[1,1-dimethyl-2-{(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, triethylene glycol bis[(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], etc. The amount of these phenol-based antioxidants added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, per 100 parts by mass of the polyolefin-based resin.

[0082] Examples of phosphorus-based antioxidants include trisnonylphenyl phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl]phosphite, tridecyl phosphite, octyldiphenyl phosphite, di(decyl)monophenyl phosphite, di(tridecyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, bis(2,4-ditert-butylphenyl)pentaerythritol diphosphite, bis(2,6-ditert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tritert-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetra(tridecyl)isopropylidenediphenol diphosphite, tetra(tridecyl)-4,4'-n-butylidenebis(2- tert-butyl-5-methylphenol) diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane triphosphite, tetrakis(2,4-ditert-butylphenyl) biphenylene diphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2'-methylenebis(4,6-tert-butylphenyl)-2-ethylhexyl phosphite, 2 ,2'-methylenebis(4,6-tert-butylphenyl)-octadecyl phosphite, 2,2'-ethylidenebis(4,6-di-tert-butylphenyl)fluorophosphite, tris(2-[(2,4,8,10-tetrakis-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]ethyl)amine, phosphite of 2-ethyl-2-butylpropylene glycol and 2,4,6-tri-tert-butylphenol, etc. The amount of these phosphorus-based antioxidants to be added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, based on 100 parts by mass of the polyolefin resin.

[0083] Examples of the thioether-based antioxidant include dialkyl thiodipropionates such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, and pentaerythritol tetra(β-alkylthiopropionic acid) esters. The amount of these thioether-based antioxidants added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the polyolefin resin.

[0084] Examples of the hindered amine light stabilizer include 2,2,6,6-tetramethyl-4-piperidyl stearate, 1,2,2,6,6-pentamethyl-4-piperidyl stearate, 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2 ,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, bis(2,2,6,6-tetramethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,4,4-pentamethyl-4-piperidyl)-2-butyl-2-(3,5-ditert-butyl-4-hydroxyethyl) dibenzyl)malonate, 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol / diethyl succinate polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-morpholino-s-triazine polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-tert-octylamino-s-triazine polycondensate, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4 -piperidyl)amino)-s-triazin-6-yl]-1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl]-1,5,8-12-tetraazadodecane, 1,6,11-tris[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazin-6-yl]aminoundecane, 1,6,11-tris[2,4-bis(N-butyl-N-(1,2,2,6,Examples of the hindered amine compounds include 6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl)aminoundecane. The amount of these hindered amine-based light stabilizers added is preferably 0.001 to 30 parts by mass, more preferably 0.05 to 10 parts by mass, based on 100 parts by mass of the polyolefin-based resin.

[0085] Examples of the ultraviolet absorber include 2-hydroxybenzophenones such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone); 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'- 2-(2'-hydroxyphenyl)benzotriazoles such as 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)benzotriazole, 2,2'-methylenebis(4-tert-octyl-6-(benzotriazolyl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-carboxyphenyl)benzotriazole; phenyl Benzoates such as ricinate, resorcinol monobenzoate, 2,4-ditert-butylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, 2,4-ditert-amylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, hexadecyl-3,5-ditert-butyl-4-hydroxybenzoate; substituted oxanilides such as 2-ethyl-2'-ethoxyoxanilide, 2-ethoxy-4'-dodecyloxanilide; ethyl-α-cyano-β,β-diphenylacrylate, methyl and triaryl triazines such as 2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine, 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-s-triazine, and 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine. The amount of these ultraviolet absorbers to be added is preferably 0.001 to 30 parts by mass, more preferably 0.05 to 10 parts by mass, based on 100 parts by mass of the polyolefin resin.

[0086] Furthermore, if necessary, it is preferable to add a known neutralizing agent to neutralize the residual catalyst in the polyolefin resin. Examples of the neutralizing agent include fatty acid metal salts such as calcium stearate, lithium stearate, and sodium stearate, and fatty acid amide compounds such as ethylene bis(stearamide), ethylene bis(12-hydroxystearamide), and stearic acid amide, and these neutralizing agents may be used in combination.

[0087] Furthermore, the resin composition of the present invention may further contain, as necessary, metal salts of carboxylates such as sodium-2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate, lithium-2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate, aluminum hydroxybis[2,2'methylenebis(4,6-di-tert-butylphenyl)phosphate], sodium benzoate, aluminum 4-tert-butylbenzoate, sodium adipate, and disodium bicyclo[2.2.1]heptane-2,3-dicarboxylate, dibenzylidene sorbitol, bis(methylbenzylidene)sorbitol, bis(3,4-dimethylbenzyl)phosphate, and the like.

[0043] Nucleating agents such as aromatic carboxylic acid metal salts, alicyclic alkyl carboxylic acid metal salts, aluminum p-tert-butylbenzoate, aromatic phosphate metal salts, dibenzylidene sorbitols, and the like may also be blended.

[0088] Furthermore, to the resin composition of the present invention, metal soaps, hydrotalcites, triazine ring-containing compounds, metal hydroxides, phosphate ester-based flame retardants, condensed phosphate ester-based flame retardants, phosphate-based flame retardants, inorganic phosphorus-based flame retardants, (poly)phosphate-based flame retardants, halogen-based flame retardants, silicon-based flame retardants, antimony oxides such as antimony trioxide, inorganic flame retardant assistants, organic flame retardant assistants, anti-drip agents, fillers, pigments, lubricants, foaming agents, and the like may be added, if necessary.

[0089] Examples of the triazine ring-containing compound include melamine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, melamine pyrophosphate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, and 1,3-hexylenedimelamine. Examples of the metal hydroxide include magnesium hydroxide, aluminum hydroxide, calcium hydroxide, barium hydroxide, zinc hydroxide, and Kismer 5A (magnesium hydroxide: manufactured by Kyowa Chemical Industry Co., Ltd.).

[0090] Examples of the phosphate ester-based flame retardants include trimethyl phosphate, triethyl phosphate, tributyl phosphate, tributoxyethyl phosphate, trischloroethyl phosphate, trisdichloropropyl phosphate, triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, trixylenyl phosphate, octyl diphenyl phosphate, xylenyl diphenyl phosphate, trisisopropylphenyl phosphate, 2-ethylhexyl diphenyl phosphate, t-butylphenyl diphenyl phosphate, bis-(t-butylphenyl)phenyl phosphate, tris-(t-butylphenyl)phosphate, isopropylphenyl diphenyl phosphate, bis-(isopropylphenyl)diphenyl phosphate, and tris-(isopropylphenyl)phosphate. Examples of the condensed phosphate ester flame retardants include 1,3-phenylene bis(diphenyl phosphate), 1,3-phenylene bis(dixylenyl phosphate), bisphenol A bis(diphenyl phosphate), and the like. Examples of the (poly)phosphate-based flame retardant include ammonium salts and amine salts of (poly)phosphoric acids, such as ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, melamine pyrophosphate, and piperazine pyrophosphate.

[0091] Examples of inorganic flame retardant auxiliary agents include inorganic compounds such as titanium oxide, aluminum oxide, magnesium oxide, hydrotalcite, talc, and montmorillonite, and surface-treated products thereof, and various commercially available products such as TIPAQUE R-680 (titanium oxide: manufactured by Ishihara Sangyo Kaisha), Kyowamag 150 (magnesium oxide: manufactured by Kyowa Chemical Industry Co., Ltd.), DHT-4A (hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.), and Alcamizer 4 (zinc-modified hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.) can be used. Examples of organic flame retardant auxiliary agents include pentaerythritol.

[0092] Furthermore, the resin composition of the present invention may contain additives that are usually used in polyolefin resins, such as crosslinking agents, antifogging agents, plate-out inhibitors, surface treatment agents, plasticizers, lubricants, flame retardants, fluorescent agents, antifungal agents, bactericides, foaming agents, metal deactivators, release agents, pigments, processing aids, antioxidants, light stabilizers, etc., as necessary, within the range that does not impair the effects of the present invention.

[0093] The method for producing the resin composition of the present invention is not particularly limited, and it is sufficient to blend the polyolefin resin with wood flour (X), one or more polymer compounds (E) (Y), one or more selected from the group consisting of alkali metal salts (F) and ionic liquids (G) (Z), and other optional components, and any method that is commonly used can be used for this purpose. For example, the method includes dry blending using a blender or Henschel mixer, or melt blending using an extruder, Banbury mixer, kneader, or the like.

[0094] The polymer compound (E) as the component (Y) may be added as it is, or may be added after impregnating it into a carrier as necessary. To impregnate the carrier, it may be heated and mixed as it is, or may be diluted with an organic solvent as necessary, impregnated into the carrier, and then the solvent may be removed. As such a carrier, a synthetic resin filler or filler known as a bulking agent, or a flame retardant or light stabilizer that is solid at room temperature can be used, and examples thereof include calcium silicate powder, silica powder, talc powder, alumina powder, titanium oxide powder, or carriers whose surfaces are chemically modified, and the flame retardants and antioxidants listed above that are solid, etc. Among these carriers, carriers whose surfaces are chemically modified are preferred, and silica powder whose surfaces are chemically modified are more preferred. These carriers preferably have an average particle size of 0.1 to 100 μm, and more preferably 0.5 to 50 μm.

[0095] Furthermore, as a method for blending the polymer compound (E) as component (Y) into the polyolefin resin, the polymer compound (E) may be synthesized and blended while kneading the block polymer (C) and the epoxy compound (D) having two or more epoxy groups into the resin component, and at that time, one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), as component (Z), may be blended simultaneously. Alternatively, the polymer compound (E), one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), and the resin component may be mixed during molding such as injection molding to obtain a molded product. Furthermore, a masterbatch of the polymer compound (E), one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), and the polyolefin resin may be produced in advance, and this masterbatch may be blended. Furthermore, the polymer compound (E) and one or more selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G) may be mixed in advance and then blended with the polyolefin resin. Alternatively, the polymer compound (E) synthesized by adding one or more selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G) during the synthesis reaction may be blended with the polyolefin resin.

[0096] A molded article can be obtained by molding the antistatic resin composition of the present invention. The molding method is not particularly limited, and examples thereof include known molding methods such as extrusion molding, injection molding, compression molding, and laminate molding. Among them, extrusion molding is preferred in terms of antistatic properties and their durability, and the woody texture of the molded article. The extrusion molding is performed using an extruder, and a specific method thereof is, for example, to feed the resin composition to a hopper of the extruder, mechanically melt-knead it in the extruder, and extrude it into the air through a die to form a molded article. As the extruder, a known extruder equipped with a single or twin screw is used, and kneading and extrusion molding of each component are performed by a single extruder, which has the advantages of being simple to operate and high productivity. The molded article of the present invention has antistatic properties, the antistatic properties last, and has an excellent woody texture. When the molded article of the present invention is used and strength or rigidity is required (for example, building materials such as flooring materials), it is also preferable to laminate the molded article of the present invention on a resin substrate as an underlay. As the resin used as the resin substrate, synthetic resins, particularly thermoplastic resins, are used without any restrictions, but among these thermoplastic resins, ABS resin, ASA resin, vinyl chloride resin, or a mixture of these resins are preferred from the viewpoints of impact resistance, rigidity, flame retardancy, and weather resistance.

[0097] In terms of the antistatic property and its durability, and the wood-like texture of the molded product of the present invention, it is preferable that the surface of the molded product is provided with irregularities, because the contact area is small, making it difficult for static electricity to occur due to friction, and the surface area is large, making it easy to discharge. Furthermore, the irregularities are preferable because they give a wood-like texture like that of natural wood. The method of forming the surface irregularities is not particularly limited, and specific examples include a chemical roughening method in which the surface is treated with a chemical agent, a physical roughening method in which the surface is treated with laser irradiation, a mechanical roughening method in which the surface is treated with a metal brush, sandpaper, etc., and a molding method in which irregularities are provided on the surface of the skin layer of a molding machine mold and formed simultaneously with extrusion, etc. Among these, in terms of the operability of the treatment, the antistatic properties and their sustainability of the molded product, and the wood-like texture of the molded product, it is preferable to perform surface treatment or sanding with sandpaper for the molded product of the present invention.

[0098] The antistatic resin composition and molded article thereof of the present invention have excellent antistatic properties and their durability, and further have an excellent wood-like texture, and therefore are suitably used for construction and building materials, such as floor boards, fence materials, frameworks and moldings, window and door shapes, shingles, roofing materials, siding, wall materials, residential interior materials, residential exterior materials, verandas, terraces, balconies, louvers, deck materials, flooring materials, fence materials, handrail materials, siding materials, pipe materials, etc., or automotive materials, such as vehicle interior materials, internal panels, rear shelves, side moldings, spare tire covers, etc., or civil engineering materials, such as promenades, park facilities, wharves, boardwalks, bridges, etc., or consumer / industrial applications, such as picnic tables, benches, pallets, chairs, desks, furniture, handrails, etc. EXAMPLES

[0099] The present invention will be described in more detail below using examples, but the present invention is not limited to these. According to the following production example, the polymer compound (E) which is the component (Y) of the present invention was produced. In the following production example, the number average molecular weight of the polyether (b) was calculated by the following <Method of calculating number average molecular weight from hydroxyl value>, and the number average molecular weights of the polyester (a) and the block polymer (C) were calculated by the following <Method of measuring number average molecular weight based on polystyrene conversion>. The molecular weight of the polypropylene glycol diglycidyl ether was calculated from the epoxy equivalent. As the wood flour of component (X), a commercially available product, Ecomills Super Feeder #100 manufactured by Sankyo Seifun Co., Ltd., was used.

[0100] <Calculation method of number average molecular weight from hydroxyl value> The hydroxyl value was measured by the following hydroxyl value measurement method, and the number average molecular weight (hereinafter also referred to as "Mn") was determined by the following formula. Number average molecular weight = (56110 x 2) / hydroxyl value

[0101] <Hydroxyl value measurement method> Reagent A (acetylating agent) (1) Triethyl phosphate 1560mL (2) Acetic anhydride 193 mL (3) Perchloric acid (60%) 16g Mix the above reagents in the order of (1) → (2) → (3). Reagent B Mix pyridine and pure water in a volume ratio of 3:1. Reagent C Add 2 to 3 drops of phenolphthalein solution to 500 mL of isopropyl alcohol and neutralize with 1N KOH aqueous solution. First, weigh out 2 g of sample into a 200 mL Erlenmeyer flask, add 10 mL of triethyl phosphate, and heat to dissolve. Add 15 mL of Reagent A, plug with a stopper, and shake vigorously. Add 20 mL of Reagent B, plug with a stopper, and shake vigorously. Add 50 mL of Reagent C. Titrate with 1N KOH aqueous solution and calculate using the formula below. Hydroxyl value [mgKOH / g] = 56.11 × f × (TB) / S f: Factor of 1N-KOH solution B: Blank test titration volume [mL] T: Test titer [mL] S: Sample amount [g]

[0102] <Method for measuring number average molecular weight based on polystyrene conversion> The number average molecular weight (hereinafter also referred to as "Mn") was measured by gel permeation chromatography (GPC). The measurement conditions for Mn were as follows: Equipment: GPC equipment manufactured by JASCO Corporation Solvent: Chloroform Reference material: Polystyrene Detector: Differential refractometer (RI detector) Column stationary phase: Showa Denko Co., Ltd. Shodex LF-804 Column temperature: 40℃ Sample concentration: 1mg / 1mL Flow rate: 0.8mL / min. Injection volume: 100μL

[0103] [Production Example 1] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 122 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the temperature was gradually raised from 170°C to 215°C while polymerization was continued at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-1. The number average molecular weight Mn of the obtained polyester (a)-1 was 2931. Next, 205 g of the obtained polyester (a)-1, 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.4 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-1 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-1 having a structure with carboxyl groups at both ends was 22109. To 392 g of the obtained block polymer (C)-1 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out at 240°C for 3 hours under reduced pressure, thereby obtaining 396 g of polymer compound (E)-1.

[0104] [Production Example 2] 207 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 153 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 32 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 20 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.4 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-2 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-2 having a structure with carboxyl groups at both ends was 22302. To 429 g of the obtained block polymer (C)-2 having a structure with carboxyl groups at both ends, 3.9 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 434 g of polymer compound (E)-2.

[0105] [Production Example 3] 196 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 96 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 80 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 50 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.3 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-3 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-3 having a structure having carboxyl groups at both ends was 21134. To 376 g of the obtained block polymer (C)-3 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 380 g of polymer compound (E)-3.

[0106] [Production Example 4] 209 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 163 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 24 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 15 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.5 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-4 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-4 having a structure with carboxyl groups at both ends was 22485. To 396 g of the obtained block polymer (C)-4 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 400 g of polymer compound (E)-4.

[0107] [Production Example 5] 189 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 57 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 112 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 70 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-5 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-5 having a structure having carboxyl groups at both ends was 20372. To 396 g of the obtained block polymer (C)-5 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 400 g of polymer compound (E)-5.

[0108] [Production Example 6] 202 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 135 g of polyethylene glycol having a number average molecular weight of 2000 as compound (b1)-2 of polyether (b) having hydroxyl groups at both ends, 45 g of polytetramethylene glycol having a number average molecular weight of 2000 as compound (b2)-2 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-6 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-6 having a structure with carboxyl groups at both ends was 12631. To 397 g of the obtained block polymer (C)-6 having a structure with carboxyl groups at both ends, 6.3 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 405 g of polymer compound (E)-6.

[0109] [Production Example 7] 200 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 135 g of polyethylene glycol having a number average molecular weight of 4000 as compound (b1)-3 of polyether (b) having hydroxyl groups at both ends, 45 g of polytetramethylene glycol having a number average molecular weight of 4000 as compound (b2)-3 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-7 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-7 having a structure with carboxyl groups at both ends was 25243. To 398 g of the obtained block polymer (C)-7 having a structure with carboxyl groups at both ends, 3.2 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 402 g of polymer compound (E)-7.

[0110] [Production Example 8] A separable flask was charged with 97 g of 1,4-cyclohexanedimethanol, 112 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the temperature was gradually raised from 170°C to 215°C while polymerization was continued at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-2. The number average molecular weight Mn of the obtained polyester (a)-2 was 2053. Next, 185 g of the obtained polyester (a)-2, 185 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 51 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.7 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-8 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-8 having a structure with carboxyl groups at both ends was 18,600. To 461 g of the obtained block polymer (C)-8 having a structure with carboxyl groups at both ends, 5.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 467 g of polymer compound (E)-8.

[0111] [Production Example 9] A separable flask was charged with 135 g of 1,4-cyclohexanedimethanol, 143 g of adipic acid, 1.5 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adeka STAB AO-60, manufactured by ADEKA Corporation), and the mixture was polymerized at normal pressure for 4 hours while gradually increasing the temperature from 170°C to 215°C, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-3. The number average molecular weight Mn of the obtained polyester (a)-3 was 5347. Next, 244 g of the obtained polyester (a)-3, 94 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 26 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.1 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-9 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-9 having a structure with carboxyl groups at both ends was 31773. To 401 g of the obtained block polymer (C)-9 having a structure with carboxyl groups at both ends, 2.6 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 404 g of polymer compound (E)-9.

[0112] [Production Example 10] To 401 g of block polymer (C)-1 having a structure with carboxyl groups at both ends obtained in the same manner as in Production Example 1, 1.7 g of polypropylene glycol diglycidyl ether (number average molecular weight 304, epoxy equivalent 200 g / eq) as epoxy compound (D)-2 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 403 g of polymer compound (E)-10.

[0113] [Production Example 11] To 391 g of block polymer (C)-1 having a structure with carboxyl groups at both ends obtained in the same manner as in Production Example 1, 2.4 g of polypropylene glycol diglycidyl ether (number average molecular weight 769, epoxy equivalent 471 g / eq) as epoxy compound (D)-3 was added, and the mixture was polymerized at 240°C for 3 hours under reduced pressure, thereby obtaining 394 g of polymer compound (E)-11.

[0114] [Production Example 12] 391 g of block polymer (C)-1 having a structure with carboxyl groups at both ends, obtained in the same manner as in Production Example 1, was charged with 2.1 g of bisphenol F diglycidyl ether (epoxy equivalent: 170 g / eq) as epoxy compound (D)-4, and the mixture was polymerized at 240°C for 3 hours under reduced pressure, thereby obtaining 394 g of polymer compound (E)-12.

[0115] [Production Example 13] A separable flask was charged with 124 g of hydrogenated bisphenol A, 84 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adeka STAB AO-60, manufactured by ADEKA Corporation), and the mixture was gradually heated from 170°C to 215°C while undergoing polymerization at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-4. The number average molecular weight Mn of the obtained polyester (a)-4 was 2922. Next, 190 g of the obtained polyester (a)-4, 133 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 37 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.1 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-10 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-10 having a structure having carboxyl groups at both ends was 21500. To 391 g of the obtained block polymer (C)-10 having a structure with carboxyl groups at both ends, 3.7 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-13.

[0116] [Production Example 14] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 122 g of adipic acid, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the mixture was polymerized at normal pressure for 4 hours while gradually increasing the temperature from 170°C to 215°C, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-5. The number average molecular weight Mn of the obtained polyester (a)-5 was 2931. Next, 206 g of the obtained polyester (a)-5, 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of an antioxidant (Adekastab AO-60), and 3.3 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-11 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-11 having a structure having carboxyl groups at both ends was 22109. To 392 g of the obtained block polymer (C)-11 having a structure with carboxyl groups at both ends, 4.4 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-14.

[0117] [Production Example 15] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 123 g of adipic acid, 0.1 g of phthalic anhydride, 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, ADK STAB AO-60, manufactured by ADEKA CORPORATION), 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, and 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the proportion of polytetramethylene glycol (b2) was 25 mol % relative to the total mole number of polyethylene glycol and polytetramethylene glycol), and polymerization was carried out at normal pressure for 4 hours while gradually increasing the temperature from 170° C. to 215° C. 3.5 g of zirconium octylate was added, and polymerization was carried out under reduced pressure for 7 hours while gradually increasing the temperature from 215° C. to 240° C. to obtain a polymer. The number average molecular weight Mn of the obtained polymer was 22,109. To 392 g of the obtained polymer, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours to obtain 396 g of polymer compound (E)-15.

[0118] [Examples 1 to 22 and Comparative Examples 1 to 4] The antistatic resin composition of the present invention was obtained by blending based on the compounding amounts (parts by mass) shown in Tables 1 to 4 below. The obtained resin composition was granulated at 200°C and 6 kg / hour using a twin-screw extruder (PCM30, 60 mesh) manufactured by Ikegai Corporation to obtain pellets. The obtained pellets were molded using a horizontal injection molding machine (NEX80: manufactured by Nissei Plastic Industrial Co., Ltd.) under processing conditions of a resin temperature of 200°C and a mold temperature of 40°C to obtain a test piece-1 (100 mm x 100 mm x 3 mm). In addition, the surface of the test piece-1 was sanded (polished) 20 times with sandpaper #500 (roughness) to obtain a test piece-2. Using the obtained test pieces-1 and -2, the surface resistivity (SR value) was measured as follows, and the antistatic property and its durability were evaluated. In addition, using the obtained test piece-2, an evaluation test of the wood texture of the molded product was performed as follows. The results are shown in Tables 1 to 4. In the same manner as in the examples, evaluation was performed using comparative antistatic agent-1 in the blending amount shown in Table 5. The results are shown in Table 5.

[0119] <Surface resistivity (SR value) measurement method> The obtained test piece-1 was stored under conditions of temperature 25°C and humidity 50%RH immediately after molding, and after storage for 1 day and 30 days after molding, the surface resistivity (Ω / □) was measured under the same atmosphere using an R8340 resistance meter manufactured by Advantest Corporation under conditions of an applied voltage of 100V and an application time of 1 minute. Measurements were performed at 5 points on each of 5 test pieces, and the average value was calculated. In addition, the obtained test piece-2 was stored under conditions of temperature 25°C and humidity 50%RH immediately after sanding, and after storage for 1 day and 30 days after sanding, the surface resistivity (Ω / □) was measured under the same atmosphere using an R8340 resistance meter manufactured by Advantest Corporation under conditions of an applied voltage of 100V and an application time of 1 minute. Measurements were performed at 5 points on each of 5 test pieces, and the average value was calculated.

[0120] <Test method for evaluating the wood texture of molded products> The appearance of the obtained test piece-2 was visually observed and rated on a 5-point scale from 1 to 5. Rating 1 is the appearance closest to natural wood and has the most excellent wood texture, and as the value increases, the wood texture becomes poorer. Rating 5 is the poorest wood texture.

[0121] [Table 1] *1: HDPE: High density polyethylene resin (Melt flow rate = 8g / 10min (ISO1133, 190℃ x 2.16kg)) *2: Wood flour: Sankyo Seiko Co., Ltd., Eco Mills Super Feeder #100 *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-18

[0122] [Table 2] *1: HDPE: High density polyethylene resin (Melt flow rate = 8g / 10min (ISO1133, 190℃ x 2.16kg)) *2: Wood flour: Sankyo Seiko Co., Ltd., Eco Mills Super Feeder #100 *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-18

[0123] [Table 3] *1: HDPE: High density polyethylene resin (Melt flow rate = 8g / 10min (ISO1133, 190℃ x 2.16kg)) *2: Wood flour: Sankyo Seiko Co., Ltd., Eco Mills Super Feeder #100 *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-18

[0124] [Table 4] *1: HDPE: High density polyethylene resin (Melt flow rate = 8g / 10min (ISO1133, 190℃ x 2.16kg)) *2: Wood flour: Sankyo Seiko Co., Ltd., Eco Mills Super Feeder #100 *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-18

[0125] [Table 5] *1: HDPE: High density polyethylene resin (Melt flow rate = 8g / 10min (ISO1133, 190℃ x 2.16kg)) *2: Wood flour: Sankyo Seiko Co., Ltd., Eco Mills Super Feeder #100 *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-18

[0126] From the above, it is seen that the antistatic resin composition of the present invention can provide a molded article having excellent antistatic performance and its durability, and having an excellent wood-like texture.

Claims

1. An antistatic resin composition comprising, relative to 100 parts by mass of a polyolefin resin, 1 to 200 parts by mass of the following component (X), 1 to 60 parts by mass of the following component (Y), and 0.01 to 15.0 parts by mass of the following component (Z): (X) Ingredient: Wood flour. Component (Y): An antistatic agent containing one or more polymeric compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and polytetramethylene glycol (b2). Component (Z): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

2. 2. The antistatic resin composition according to claim 1, wherein the polymer compound (E) is obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.

3. 3. The antistatic resin composition according to claim 2, wherein the polymer compound (E) has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which the blocks are bonded via an ester bond or an ether bond formed by a reaction between a hydroxyl group or a carboxyl group at an end of the polyester (a), a hydroxyl group at an end of the polyether (b), and an epoxy group of the epoxy compound (D) or a hydroxyl group formed by a reaction of an epoxy group.

4. 4. The antistatic resin composition according to claim 3, wherein the polymer compound (E) has a structure in which a block polymer (C) having carboxyl groups at both ends thereof, which is formed by repeatedly and alternately bonding the polyester block (A) and the polyether block (B) via ester bonds, and the epoxy compound (D) are bonded via ester bonds.

5. 2. The antistatic resin composition according to claim 1, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

6. 3. The antistatic resin composition according to claim 2, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

7. 4. The antistatic resin composition according to claim 3, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

8. 5. The antistatic resin composition according to claim 4, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

9. A molded article obtained from the antistatic resin composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Wood composite

    JP2007169350A

  • Resin molded body and resin laminate

    JP2014105284A